Characteristics of expert nurses' assessment of insertion sites for peripheral venous catheters in elderly adults with hard‐to‐find veins. Issue 1 (6th October 2020) - Masamoto, Tsuneko; Yano, Rika
Abstract: Aim: To clarify the characteristics of expert nurses' assessments when selecting an insertion site for a peripheral venous catheter (PVC). Methods: Participants were 11 competent (control group) and 13 expert nurses. Using a simulated patient, we recorded the procedures participants followed when selecting a site for a PVC insertion. The researchers interviewed the nurses after the procedure by asking targeted questions about the site selection to clarify the factors influencing that selection. During the interview, a video of that nurse's procedure was observed, and each step performed during the procedure was investigated. Results: We identified three assessment characteristics specific to expert nurses that influenced their PVC site selection: (a) focusing on a patient's unique characteristics and choosing the appropriate procedure for that individual; (b) avoiding complications and paying attention to the patient's daily self‐care needs; and (c) carefully considering the patient's fear and fatigue during site selection and catheter insertion. Other assessments, based on the general knowledge and skill acquired by nurses in selecting a PVC site, were common to both groups: arm selection based on the patient's preference and site selection to avoid nerve injuries or complications. The control group's approach was assessed on the basis of their confidence in selecting a site for a PVC insertion. Conclusions: Expert nurses assessed the patient's individual characteristics and daily self‐care needs and helped mitigate the patient's anxiety. Our findings provide a basis for educational programs that share how expert nurses assess sites for a PVC insertion.